A new linguistic aggregation operator and its application to multiple attribute decision making - Jibin Lan; Yuwen Chen; Mengyao Ning; Zhongxing Wang (Operations Research Perspectives, 2015)
In this paper, a new linguistic aggregation operator in linguistic environment is established and the desirable properties: monotonic, focus effect, idempotent, commutative and bounded are studied. Then, a new restricted ordering relation on the n-dimensional linguistic scales is proposed which satisfies strict pareto-dominance and is restricted by a weighting vector. A practical multiple attribute decision making methodology for an uncertain linguistic environment is proposed based on the proposed operator. An example is given to illustrate the rationality and validity of the new approach to decision making application.
Keywords: 330; Linguistic aggregation operator; Linguistic environment; Ordering relation; Strict pareto-dominance; Multiple attribute decision making